ANALISIS DAMPAK LALU LINTAS DI KAWASAN SINGKAWANG GRAND MALL PADA SAAT 48% BEROPERASI - Banyu Susanto; Sutarto YM; . Said (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2016)
The construction of the Singkawang Grand Mall will impact traffic around Singkawang area Grand Mall (Jalan tani, Jalan Kesatriaan, Jalan alianyang). Changes and intensity of land use activities will certainly bring increased traffic volume. Land use change when not in anticipation of it well can lead to problems in the operation of the Singkawang Grand Mall. A problem that caused IE not the share of road capacity with volume road after 100% operational Singkawang Grand Mall. This research aims to know the magnitude of the force generation and dirimbulkan by the Singkawang Grand Mall, to know the capacity of the Farm Road, kesatriaan Road, and the road Alianyang before and after operation of Singkawang Grand Mall in the study take sampling data Singakwang grand Mall at present operates 48% of the test results of the research are as follows: 1) farmer's Road performance level before operating 100% acquired Grand Mall of Singkawang 0.325 or enter into A service level; 2) after operating 100% level of service in the way Farmers to 0.60 or into alternative b. service levels obtained from this research such as; menambahan Farm Road Width of 6 meters to 7 meters so that the level of service "Jalan Tani" back A.   Kata Kunci:Traffic Generation, The Pull, The Capacity.